2011
DOI: 10.1071/he11210
|View full text |Cite
|
Sign up to set email alerts
|

Children's consumption of energy-dense nutrient-poor foods, fruit and vegetables: are they related? An analysis of data from a cross sectional survey

Abstract: The positive associations found between EDNP foods point towards the existence of a high-risk group of children who frequently consume a variety of EDNP foods and drinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In the current study, the JFIM was categorised into tertiles so that low, middle and high tertiles denoted scores in the ranges [0–5], [68], and [9–25], respectively. The JFIM was also treated as a continuous variable when examining the mean difference in the JFIM between 2010 and 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the JFIM was categorised into tertiles so that low, middle and high tertiles denoted scores in the ranges [0–5], [68], and [9–25], respectively. The JFIM was also treated as a continuous variable when examining the mean difference in the JFIM between 2010 and 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Reporting on individual, rather than the overall or combined frequency of junk foods, may hide the true extent of junk food consumption among children and adolescents as these foods are typically eaten in combination, for example potato chips and soft drink [6]. Information on the overall rating of children’s diets may prove useful in the development of strategies aimed to reduce consumption and prevent childhood obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that there is considerable scope for improving children's eating behaviours. [14][15][16][17][18] In Western Australia, the context of the present study, 34% of boys and 35% of girls consumed snacks or meals from fast food chains at least once per week. Confectionary and cereal bars were consumed daily by 33% of boys and 39% of girls.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous Australian and New Zealand research, which found that the majority of food products available for sale [34] and directed at children [35] were considered 'less healthy' using nutrient profiling criteria. Additionally, several population-based surveys have found that Australian children regularly consume high ED, nutrient-poor foods [17][18][19]. While it is important to encourage children to meet dietary recommendations and energy needs through healthful food intake and limited intake of high ED, nutrient-poor foods, additional strategies targeting the retail food market have the potential to assist in moderating children's dietary energy density and energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Several population-based surveys have found that Australian children regularly consume discretionary foods [17][18][19]. The Australian National Health Survey found that just under 40% of the total energy consumed by 4-to 13-year-old children came from discretionary foods [19].…”
Section: Introductionmentioning
confidence: 99%